The Role of Agency Banking in Enhancing Financial Inclusion; a Case Study of Mukono District - Raymond Lhwanzo (Uganda Christian University, 2024)
This study examines the role of agency banking in enhancing financial inclusion in Uganda, with a focus on Equity and Stanbic Banks in Mukono Municipality. The specific objectives were to assess the impact of agency banking in terms of accessibility, affordability, and service usage on financial inclusion. A descriptive research design was adopted, and a sample of 32 respondents, including bank managers, agents, employees, and supervisors, was selected using Krejcie and Morgan’s sampling method. A pilot study was conducted to ensure the reliability and validity of the research instruments. The findings indicated that agency banking significantly improves financial inclusion by increasing access to banking services, particularly in rural areas, through the reduction of physical barriers and the provision of services in local languages. Affordability, characterized by reasonable transaction fees and favorable lending policies, also played a key role in boosting customer participation. However, challenges such as liquidity constraints at agent locations and some physical obstacles remained unaddressed. In conclusion, agency banking has positively contributed to financial inclusion in Uganda, but ongoing efforts are required to resolve the existing challenges and further enhance the accessibility and effectiveness of agency banking services
Undergraduate research